Competition on the LNG market – consequences for the EU - Lont, Paweł (Konkurencja na rynku LNG – konsekwencje dla Unii Europejskiej, 2020)
The aim of this article is to assess the impact of the natural gas sector’s gradual transition towards a globally-traded commodity market for EU economies. The literature review provides evidence of regulatory, technological and business practice changes that have led to the development of a global gas market. A statistical analysis of the price spreads between the regions and of the differences in the LNG shipment costs is performed to verify whether competition over cargoes at a global level observed over the last years is not temporary. The results confirm that the market-based price indices have become a more relevant and popular form of price reference for short and long-term LNG supply contracts than oil indexation. The author concludes that the transition from regional markets to a global market has brought multiple benefits to EU economies that can be largely lost if Asian economies will be ready to pay substantial premiums for LNG cargoes in the future
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 6, s. 127-141